Development and biological evaluation of a novel CEACAM6-targeted PET tracer for distinguishing malignant nodules in early-stage lung adenocarcinoma. - Zhu, Keying; Tang, Shimin; Pan, Donghui; Wang, Xinyu; Xu, Yuping; Yan, Junjie; Wang, Lizhen; Chen, Chongyang; Yang, Min (European Journal of Nuclear Medicine & Molecular Imaging, 2025)
Purpose: Low-dose CT (LDCT) screening effectively reduces lung adenocarcinoma (LUAD) mortality. However, accurately evaluating the malignant potential of indeterminate lung nodules remains a challenge. Carcinoembryonic antigen cell adhesion molecule 6 (CEACAM6), a potential biomarker for distinguishing benign pulmonary nodules from LUAD, may be leveraged for noninvasive positron emission tomography (PET) imaging to aid LUAD diagnosis. Methods: This study utilized mRNA, protein, and survival datasets of LUAD patients, along with an animal model of malignant pulmonary nodules, to investigate CEACAM6 expression specificity and its correlation with LUAD. Targeting ligands for CEACAM6 were designed using the Rosetta platform, labeled with [68Ga]Ga, and screened through high-throughput PET imaging to identify the optimal tracer. Results: CEACAM6 was found to be specifically overexpressed in LUAD and was significantly associated with poor prognosis and disease progression. In vivo, [68Ga]Ga-NODA-P3 demonstrated high specificity for delineating CEACAM6-positive A549 xenografts, a LUAD model, via PET imaging, achieving a highest target-to-background ratio of 7.68 ± 0.44. Region of interest (ROI) analysis showed significantly higher tracer uptake in A549 xenografts compared to CEACAM6-negative Huh7 xenografts (a hepatocellular carcinoma model) at 30 min post-injection (1.81 ± 0.10%ID/g vs. 0.54 ± 0.06%ID/g). Pre-treatment with an excess of unlabeled NODA-P3 significantly reduced tumor uptake to 0.52 ± 0.07%ID/g. Conclusion: These preclinical findings indicate that [68Ga]Ga-NODA-P3 is a candidate radiotracer for the non-invasive visualization of CEACAM6-positive LUAD, demonstrating favorable imaging contrast. Although the current tumor uptake limits its immediate clinical application, ongoing optimization efforts are expected to improve its efficacy, enabling earlier and more accurate diagnosis of malignant pulmonary nodules in LUAD.